Stratigraphic guide to the Cromer Knoll, Shetland and Chalk Groups, North Sea and Norwegian Sea: - Gradstein, F.M.; Waters, C.N.; Charnock, M.; Munsterman, D.K.; Hollerboach, M.; Brunstad, H.; Hammer, O.; Vergara, L. (2016)
This guide provides a major revision and update of the stratigraphy of the Cromer Knoll, Shetland